ANALISIS TEMPORAL PERUBAHAN TUTUPAN LAHAN TAMAN WISATA ALAM WERA KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Vivaldy, Jordy; Wahid, Abdul; Misrah, Misrah; Akhbar, Akhbar; Arianingsih, Ida; Rahmat, Rahmat (Jurnal Warta Rimba, 2021)
Changes in land cover in Wera Nature Park can change every year, therefore the researcher wants to analyze the temporal changes in land cover in the Wera Nature Park, Sigi Regency, Central Sulawesi Province. Data and information regarding changes in forest cover in tourist parks are needed as a consideration for decision making for forest area management. Remote sensing (remote sensing) is a technology that can be applied to obtain data and information about land cover in Wera tourism parks. Analysis of land use change using spatial data that is temporal in nature is very useful to see the locations where changes in land use have occurred. This study aims to see the extent of changes in cover over a period of five years in natural tourism areas from 2015 - 2019 using Landsat 8 imagery.This research was conducted from August 2020 to March 2021, which is located in the Wera Nature Park, Sigi Regency, Central Sulawesi Province. In data collection, there are two sources used, namely primary data which is data that is directly obtained in the field. Secondary data is data that is needed to support primary data. Sekuder data is in the form of Map of Designation of Indonesian Forest Areas according to the Decree of the Minister of Forestry Number 869 / Menhut-II / 2014, the administrative map of Daenggune Village in the form of roads, rivers and others as well as Landsat 8 imagery in 2015 and 2019.Keywords : Land cover in the Wera Nature Park, Landsat 8